2019
DOI: 10.1101/689943
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Cannabidiol attenuates seizures and EEG abnormalities in Angelman syndrome model mice

Abstract: Angelman syndrome (AS) is a neurodevelopmental disorder characterized by intellectual disability, lack of speech, ataxia, EEG abnormalities, and epilepsy. Seizures in AS individuals are often refractory to existing antiepileptic medications. Therefore, there is an unmet need for better seizure control, which could potentially improve other symptomatic domains such as cognitive function.Cannabidiol (CBD), a major phytocannabinoid constituent of cannabis, has anti-seizure activity and behavioral benefits in prec… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
6
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 41 publications
(66 reference statements)
5
6
0
Order By: Relevance
“…In agreement with previous studies [Gu et al, 2019; Sonzogni et al, 2018], Ube3a m−/p+ mice had a significant impairment in marble‐burying behavior relative to WT littermates: they spent much less time burying marbles and buried significantly fewer marbles. IGF‐2 injection 20 min before the marble‐burying test fully reversed this impairment.…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…In agreement with previous studies [Gu et al, 2019; Sonzogni et al, 2018], Ube3a m−/p+ mice had a significant impairment in marble‐burying behavior relative to WT littermates: they spent much less time burying marbles and buried significantly fewer marbles. IGF‐2 injection 20 min before the marble‐burying test fully reversed this impairment.…”
Section: Resultssupporting
confidence: 92%
“…The only behavior that was found unaffected by either IGF‐2 or M6P treatment was the open field behavior, which was assessed using distance traveled and center crossing, a measure believed to reflect anxiety. Similarly to what was reported in previous studies [Born et al, 2017; Gu et al, 2019; Huang et al, 2013; Mandel‐Brehm et al, 2015; Sonzogni et al, 2018], we found that AS mice have deficits in the total distance traveled during open field but not in the time spent in the center or number of entries in the open field arena. In fact, only a trend toward less time spent in the center of the open field for AS relative to WT was observed.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Thibert and Anderson have carefully explained their reports of elevated delta power in AS clinics [31,32]. Further, we reproduced Sidorov et al earlier work [46] that highlighted delta power as translational biomarker [31,33]. This phenotypic reliability paves the pathway to power spectral signatures as therapeutic windows for precision treatment within AS and beyond including other NDDs, such as Dup15q and genetic forms of ASD [47][48][49][50].…”
Section: Discussionsupporting
confidence: 68%
“…Many laboratories have used this AS mouse model of Jiang and Beaduet [11] and reported numerous characteristics that resemble core features of AS including seizure susceptibility, increased epileptiform activity, elevated delta and sleep de cits, though they vary widely on seizure induction methods, background strain and EEG collection techniques [15,[27][28][29][30][31][32][33]. In corroboration and extension, we quanti ed seizure susceptibility in Ube3a-del mice on the seizure resistant C57BL/6J background strain instead of the 129S1/SvImJ often used for seizure studies in AS, since the C57BL/6J's are resistant to seizures [34].…”
Section: Introductionmentioning
confidence: 99%